Comparing the Impact of Bullying Victimization on Drug Use and Weapon Carrying among Male and Female Middle and High School Students: A Partial Test of General Strain Theory. Issue 12 (1st December 2020) - Brady, Caitlin M.; Baker, Thomas; Pelfrey, William V.
ABSTRACT: Prior research testing general strain theory (GST) suggests potential differences in how males and females respond to strain. Using a sample of 3, 139 middle and high school students (1, 515 males and 1, 624 females), this study evaluates male and female delinquent coping behaviors to traditional bullying and cyberbullying victimization. Three delinquent coping behaviors are investigated: soft drug use, hard drug use, and weapon carrying. This study also examines the impact of bullying on anticipated strain and tests whether anticipated strain mediates the relationship between bullying and delinquency. Results from group-based structural equation models indicate sex differences in the effect of bullying on delinquent coping behavior. Specifically, bullying victimization has a significantly larger association with anticipated strain for males and cyberbullying victimization has a significantly larger association with drug use and weapon carrying for males. Anticipated strain partially mediates the relationship between bullying and delinquency. Policy implications and suggestions for future research are discussed.